Qualidade do pescado avaliado para consumo pelo exército brasileiro na Amazônia Ocidental de 2015 a 2020 - (:unkn) unknown (Universidade Brasil, 2021)
In the concept of the general principles of food hygiene, food safety is cur rently one of the main concerns of institutions that produce meals for large audien ces. Specifically in the Brazilian Army, there are the Food Inspection and Bromato logy Laboratories (LIAB) that carry out the quality and identity control of all foodstuffs acquired by the institution. The laboratories are found in 18 units called provider bo dies and are headed by veterinarians. Currently, around twenty thousand soldiers are distributed in the study area, Western Amazon, which covers the states of Acre, A mazonas, Rondônia and Roraima. Fish acquired from family farming and from com panies with inspection carried out by the Federal Inspection Service (SIF) are part of the protein menu of this target audience. Therefore, the aim of this study was to in vestigate the quality of the fish acquired, through a historical survey of the LIAB phy sical-chemical and microbiological analysis reports from 2015 to 2020. Thus, it was found that out of the 528,954 tons of fish acquired in the period studied, 5% were considered unfit for consumption, which corresponds to 24,000 tons. These showed changes in the physicochemical analysis, as the samples tested positive for traces of hydrogen sulphide (H2S) and ammonia (NH3), in addition to pH above 7, characteri zing the product's deterioration process, in addition to hiding information from the product on the label. The study found temperature records above -12°C and conse quent recrystallization, as well as three batches weighing less than those described on the packaging, including the glaciation test, in one shipment exceeding the weight limit. As for microbiological analyses, Sal-monella was absent for all samples, for co agulase-positive Staphylococcus (CFU/g), of 46 analyses, 27 showed growth (<5x10³ CFU/g) and five without representative growth (<10 CFU/g). / g). There were 36% of the reports with considerations, justified receipts and notified suppliers. The approval or disapproval of food in the LIAB is important to ensure the hygienic-sanitary quality standard and thus maintain the health of the troops.
Keywords: Físico-químico; Pescado; Microbiológico; Estafilococos; Salmonella; Produção Animal